Active Bi- and Multistability in Cooperative Microactuator Systems - Kohl, Manfred; Ament, Christoph; Arivanandhan, Gowtham; Bechtold, Tamara; Conrad, Peter; Croce, Sipontina; Gottwald, Vincent; Hoffmann, Martin; Hubertus, Jonas; Kopp, Alexander; Li, Zixiong; Olbrich, Michael; et al. (Sensors and Actuators Reports, 2025)
The smart coupling of microactuators to cooperative microactuator systems enables new functionalities like active bi- and multistability requiring no external force for switching between stable states. This review explores different concepts of cooperative microactuator systems combining microactuation based on either the same or different transducer principles. The transducer principles comprise electrostatic, magnetic, dielectric elastomer and shape memory effects as well as combinations thereof. Thereby, active bi-/multistable switching is achieved via selective control of the microactuators using diverse control signals based on thermal, electrical or magnetic stimuli. The combination of the microactuators in confined space gives rise to various coupling effects and cross-sensitivities that need to be considered. In the following, the engineering aspects of material properties, microsystems design and fabrication, as well as experimental and numerical characterization of system performances and dependencies on design parameters will be discussed. The presented microactuator systems will be assessed with respect to their energy characteristics and critical forces for switching. Their application potential will be highlighte
Keywords: Cooperative microactuator systems; Bistability; Multistability; Metastable energy systems; Microtechnology; MEMS